Peran Biro Pemerintahan dan Otonomi Daerah Provinsi Jawa Timur Dalam Penyelenggaraan Kerjasama Antar Daerah - Pratiwi, Adellia Mega; baikhaqi, Vaizal; Wardhana, Muhammad Fiqih Samudera (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The implementation of regional autonomy in Indonesia has several objectives to improve the welfare of the people in an autonomous region. The implementation of regional autonomy in Indonesia has a positive impact on the growth and development of regions in Indonesia, this has made local governments make various efforts to advance and stabilize their regions, one of which is by cooperating between regions. The Bureau of Government and Regional Autonomy of East Java, as a work unit under the Regional Secretariat of East Java Province, plays a crucial role in the implementation of government, especially related to regional autonomy. The role of the Bureau of Government and Regional Autonomy in managing inter-regional cooperation basically has a foundation as stated in Pergun No. 108 of 2021 concerning the Organizational Structure and Work Procedures of the East Java Regional Secretariat. However, challenges such as lack of coordination and communication between the central and regional governments still need to be overcome. Inter-regional cooperation has proven effective in increasing regional competitiveness and providing the best service to the community.